Changes in the anaerobic threshold in an annual cycle of sport training of young soccer players - Sliwowski, R.; Andrzejewski, M.; Wieczorek, A.; Barinow-Wojewódzki, A.; Jadczak, L.; Adrian, J.; Pietrzak, M.; Wieczorek, J. (Biology of Sport, 2013)
The aim of the study was to assess changes in the anaerobic threshold of young soccer players in an annual training cycle. A group of highly trained 15-18 year old players of KKS Lech Poznan' were tested. The tests included an annual training macrocycle, and its individual stages resulted from the time structure of the sports training. In order to assess the level of exercise capacities of the players, a field exercise test of increasing intensity was carried out on a soccer pitch. The test made it possible to determine the 4 millimolar lactate threshold (T LA 4 mmol · l-1) on the basis of the lactate concentration in blood [LA], to establish the threshold running speed and the threshold heart rate [HR]. The threshold running speed at the level of the 4 millimolar lactate threshold was established using the two-point form of the equation of a straight line. The obtained indicators of the threshold running speed allowed for precise establishment of effort intensity used in individual training in developing aerobic endurance. In order to test the significance of differences in mean values between four dates of tests, a non-parametric Friedman ANOVA test was used. The significance of differences between consecutive dates of tests was determined using a post-hoc Friedman ANOVA test. The tests showed significant differences in values of selected indicators determined at the anaerobic threshold in various stages of an annual training cycle of young soccer players. The most beneficial changes in terms of the threshold running speed were noted on the fourth date of tests, when the participants had the highest values of 4.01 m · s-1 for older juniors, and 3.80 m · s-1 for younger juniors. This may be indicative of effective application of an individualized programme of training loads and of good preparation of teams for competition in terms of players` aerobic endurance.